Risk Factors for Type 2 Diabetes in Bangladesh: A Systematic Review - T Sal-sabil; A Islam; S M Shariful Islam (Journal of Diabetology, 2016)
Diabetes is one of the most significant public health challenge in developing countries. The risk factors for diabetes are poorly understood among the Bangladeshi population. This study aimed to explore the potential risk factors for type 2 diabetes in Bangladesh. A systematic review was performed. Studies describing the risk factors for type 2 diabetes in Bangladesh published between 1994 to 2014 were included and summarized. Of the 35 studies identified, we included 14 studies that met the inclusion criteria. The prevalence of diabetes was higher among females compared to males. Fourteen common risk factors for diabetes in Bangladesh were identified, namely increased age, obesity, waist- hip ratio, social class, hypertension, family history, sedentary life style among others. The p otential risk factors differed by urban-rural areas and by gender. Several risk factors contribute to the increasing prevalence of type 2 diabetes. Our reviews suggest "metabolically-disadvantageous" body composition of more abdominal and visceral fat in Bangladeshi adults might cause higher diabetes risk at a lower BMI compared to Western population. Preventive strategies targeting to control risk factors for diabetes is a priority public health issue and should be considered for early intervention by clinicians and policy makers.